2020
DOI: 10.1002/cncr.32900
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act improved health insurance coverage and cardiovascular‐related screening rates for cancer survivors seen in community health centers

Abstract: BACKGROUND: This study assessed the impact of Affordable Care Act (ACA) Medicaid expansion on health insurance rates and receipt of cardiovascular-related preventive screenings (body mass index, glycated hemoglobin [HbA1c], low-density lipoproteins, and blood pressure) for cancer survivors seen in community health centers (CHCs). METHODS: This study identified cancer survivors aged 19 to 64 years with at least 3 CHC visits in 13 states from the Accelerating Data Value Across a National Community Health Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Fifth, comorbid conditions and functional status were also self-reported; however, the reliability and validity of BRFSS data on medical conditions have been previously validated. 2 Sixth, the heterogeneity of coverage within each insurance category in both private and public programs was not uniform and varied in terms of benefits by employer, plan, and state and may have confounded our findings.…”
Section: Limitationsmentioning
confidence: 84%
See 3 more Smart Citations
“…Fifth, comorbid conditions and functional status were also self-reported; however, the reliability and validity of BRFSS data on medical conditions have been previously validated. 2 Sixth, the heterogeneity of coverage within each insurance category in both private and public programs was not uniform and varied in terms of benefits by employer, plan, and state and may have confounded our findings.…”
Section: Limitationsmentioning
confidence: 84%
“…To assess the type of coverage, we used the question, "What is the primary source of your health care coverage?" The response options included the following: (1) plan purchased through an employer or union; (2) (8) no coverage. If the respondents indicated that they purchased insurance through the Health Insurance Marketplace, they were then asked whether it was a private plan purchased on their own or by a family member or whether they received Medicaid (public plan).…”
Section: Analytic Samplementioning
confidence: 99%
See 2 more Smart Citations
“…20 Non-expansion states saw slower rates of decline. In 2012-2013, it was 33.6%, declining to 20.3% in 2014-2015 before increasing to 22.5% in 2016-2017.…”
mentioning
confidence: 99%